Correlates of Pedestrian and Cyclist Falls in Snowy and Icy Conditions - Martin Bärwolff; Angelika Reinartz; Regine Gerike (Transactions on Transport Sciences, 2022)
Existing international studies consistently report increased numbers of pedestrian and cyclist falls in the winter months, particularly in icy/snowy conditions. Until now, reliable information on the factors contributing to these falls has been rare. This study investigates possible correlates of pedestrian and cyclist falls in icy/snowy conditions in Germany and takes into consideration factors such as behavior and surface conditions with the aim to develop recommendations for improving safety for vulnerable road users. As part of this study, 3,300 people in online surveys and 2,100 in field surveys were asked about their experiences and opinions in relation to icy/snowy conditions and winter maintenance. Of those surveyed, 1,100 pedestrians and 2,200 cyclists also reported details about their most recent fall within the last five years. Furthermore, the behavior of 7,000 pedestrians and 4,500 cyclists was observed with cameras in both snowy and other weather conditions. The presence of snow/ice itself was indicated as a reason for three quarters of pedestrian and two thirds of cyclist falls in snowy/icy conditions. For nearly all of the falls in snowy/icy conditions, surfaces were reported as poorly cleared or not cleared at all. Compared to other weather more pedestrians fell on sidewalks and less while crossing the street during snowy and icy conditions. Cyclists increased their speed on downhill sidewalks in dry conditions and reduced their speed in snowy conditions compared to flat or uphill sidewalks. Most cyclists chose to cycle on sidewalks instead of their own dedicated, but not maintained, facilities (even though they are obliged by law to cycle on the carriageway in such cases). In snowy/icy conditions, 5 % of pedestrians varied their pace or step sequence and 8 % of cyclists drove "wavy lines" or made obvious corrective steering movements, particularly on poorly maintained facilities (compared to very few of such observations in other weather conditions). Half of the respondents rated the winter maintenance at pedestrian facilities to be good and three quarters rated the maintenance at public transport stops as good. In contrast, only 12 % rated winter maintenance on cycling facilities as good. Reasons for not being satisfied included poor quality, delay and insufficient frequency of cleaning as well as the type of grit used. The lack of seamless reliably-cleaned cycle routes was listed as a major problem by most respondents. More than 50 % claimed that previously cleaned pedestrian or cyclist facilities were re-covered with snow from clearing the carriageway.